ANALISIS STUDI KELAYAKAN BISNIS UMKM JASA KONVEKSI MENGGUNAKAN PENDEKATAN BREAK EVENT POINT (BEP) DAN RETURN ON INVESTMENT (ROI): STUDI KASUS CLEMIRA KONVEKSI - Fella Vidia Fravisdh Fravisdha; Indra Hastuti (Journal of Innovative and Creativity (Joecy), 2026)
The growing demand for uniforms and daily uniforms (PDH) from government agencies, schools, and companies has encouraged the development of MSME-scale convection businesses based on a pre-order system. This study aims to analyze the financial feasibility of CLEMIRA Konveksi as an MSME providing PDH/shirt production services with a pre-order system. The study uses a quantitative descriptive approach by utilizing secondary data in the form of business feasibility calculation documents, including investment capital, working capital, revenue projections, and operational costs. The feasibility analysis is carried out through the calculation of business profits, Break Even Point (BEP), Return on Investment (ROI), and Payback Period. The results of the study indicate that the business requires a total capital of Rp206,140,000, consisting of investment capital of Rp150,000,000 and working capital of Rp56,140,000, with a projected monthly revenue of Rp60,500,000 and a net profit of Rp4,360,000 per month or Rp52,320,000 per year. The BEP value was recorded at 583 units, equivalent to Rp64,130,000 per month, with an ROI of 25.38% per year, and a payback period of approximately 3.94 years. These findings indicate that CLEMIRA Konveksi has a good level of profitability even though its break-even point is close to production capacity. Therefore, strategies to increase order volume and cost efficiency are needed to strengthen the business's safety margin. Overall, this business is considered feasible to run and has quite good development prospects.